Macrodiplodiopsis in Lophiostomataceae, Pleosporales - Wijayawardene, Nalin N.; Camporesi, Erio; Bhat, D. Jayarama; Song, Yu; Chethana, K.w. Thilini; Chukeatirote, Ekachai; Wang, Yong; Hyde, Kevin D. (Phytotaxa, 2014)
Macrodiplodiopsis desmazieri, the type species of Macrodiplodiopsis, was collected from Italy, and morpho-molecular studies were carried out. Phylogenetic analyses (maximum-likelihood, maximum parsimony and Bayesian) using combined data set of LSU, SSU and EF1-α sequences showed our strain to group in Lophiostomataceae (Pleosporales) with Misturatosphaeria uniseriata and other Misturatosphaeria spp. Floricola striata, the type species of Floricola also groups in the same clade with a close relationship with Misturatosphaeria cruciformis. The Macrodiplodiopsis clade is well supported with high bootstrap and posterior probability. Floricola striata and nine species of Misturatosphaeria are transferred to the older name Macrodiplodiopsis as new combinations.